The influence of talent management self afficay and employee engagement on employee performance - Willy Ristian; Muhamad Ehksan (Enrichment : Journal of Management, 2023)
This study aims to determine the effect of talent management, self-efficacy and employee engagement partially and simultaneously on employee performance at PT MG. The research was conducted using quantitative methods. Population In this study there were 120 employees in the MEGA BOX CTA section, the sampling technique used in this study used saturated sampling. Data was collected by questionnaire and analyzed by SMART PLS 3.0 . Data analysis techniques used include validity test, reliability test, structural equation model test, PLS-SEM, PLS model evaluation, outer model evaluation and inner model evaluation. Based on the research findings, it will help companies improve the performance of their employees, that there is a study of talent management if it is more seriously carried out, this is an effort to recruit, retain and develop employees through their talents and self-confidence so that employees can help overcome problems that often occur in work, such as undeveloped talents, lack of confidence in one's own abilities and lack of interest in one's work. Employee performance can be said to be good if the work results obtained are able to meet standards, this can be obtained one of them through the development that the company provides.